Feminisme dalam Sajak Tukhôtibu Al-Marah Al-Mishrīyah Karya Bâkhisah Al-Bâdīyah (Analisis Semiotik Roland Barthes) - Faizetul Ukhrawiyah; Muhammad Munir (Diwan : Jurnal Bahasa dan Sastra Arab, 2019)
والهدف من هذا البحث هو كشف دلائل المعاني وأسرارها الواردة في الشعر "تخاطب المرأة المصرية" كتبتها باحثة البادية. وفي تحقيق كشف هذه المعاني وتحليلها فيستخدم الباحث طريقة ونظرية "السميائية رولان بارت".  وتكون هذه النظرية أول طريقة في معرفة تلك المعاني، وتسمى ب "المعاني الحرفية"، ثم تليها الدلالة الضمنية التي تحتاج إلى إقامة إيديولوجيا، وتسمى ب " الأسطورة". ومما يحصل على هذا البحث يدل على أن هذا الشعر يضمن في المعاني المتعددة التي تدل على مذهب مؤنث الذي يحاول المساوة والعدل في حقوق النساء .  وسوف يتحقق هذا المذهب تحقيقا حسنا حين اجتمع التجديد بالتعاليم الإسلامية والتقاليدية.الكلمات المفتاحية : باحثة البادية؛ النسوية؛ السميائية رولان بارت.AbstractThis study aims to explore the meaning of the sign contained in the poem Tukhotibu al-Mar'ah al-Mishriyah by Bahisah al-Badiyah. To explore this meaning, the analysis was carried out using the semiotic theory of Roland Barthes. Roland Barthes's semiotic theory used is the meaning in the first stage or what is referred to as denotation and continued with the meaning in the second stage or connotation which is identical to the ideological operation which is called a myth. The results show that this poem contains many signs that point to feminist thinking. Feminism which is a struggle to demand equality of rights and justice for women, can be realized well if there is a combination of westernization with the teachings of Islam and traditionalism.